2008
DOI: 10.1210/jc.2008-1290
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Screening Kindreds for SDHD p.Cys11X as a Common Mutation Associated with Paraganglioma Syndrome Type 1

Abstract: The SDHD p.Cys11X mutation is a founding mutation associated with a high penetrance for paraganglial tumors of the skull base, neck, thorax, and retroperitoneum in the first four decades of life and, rarely, with malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Currently, there is no international consensus regarding intervals and specific programs. Our consortium sites suggest conventional multisection imaging by magnetic resonance imaging of the skull-base and neck, the thorax, the abdomen, and the pelvis to detect unrecognized paraganglial tumors in time (35)(36)(37). This type of surveillance will detect incidental ''other'' tumors including those of the kidneys, thyroid, and gastrointestinal stromal tumors (19,22).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no international consensus regarding intervals and specific programs. Our consortium sites suggest conventional multisection imaging by magnetic resonance imaging of the skull-base and neck, the thorax, the abdomen, and the pelvis to detect unrecognized paraganglial tumors in time (35)(36)(37). This type of surveillance will detect incidental ''other'' tumors including those of the kidneys, thyroid, and gastrointestinal stromal tumors (19,22).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 40% of all unselected male breast cancers and 10% of all female breast cancers diagnosed in Iceland are accounted for by a single mutation in BRCA2, 999del5 (28,29). Similarly, several mutations in the SDHB, SDHD, and VHL genes have been observed to occur in higher frequencies in some restricted geographic areas and most likely represent founder mutations (14,(30)(31)(32)(33)(34). For patients coming from these areas, genetic testing for the region-specific founder mutation should be offered first in the absence of obvious syndromic features.…”
Section: Discussionmentioning
confidence: 99%
“…We have described a founder deletion of exon 3 of the SDHB gene in nine patients of this same group of point mutation-negative patients (Bayley et al 2009). While founder mutations are common in the Dutch population , Zeegers et al 2004, as once again shown by the identification of the SDHB exon 3 deletion, other populations also show founder effects (Cascon et al 2008, Peczkowska et al 2008b, Opocher et al 2009), indicating that while the general frequency of SDH deletions across all paraganglioma patient populations cannot yet be established, the proportion of deletions found in the Dutch population may have wider relevance.…”
Section: Discussionmentioning
confidence: 96%